A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes) - Collins, Rupert A.; Ribeiro, Emanuell Duarte; Machado, Valéria Nogueira; Hrbek, Tomas; Farias, Izeni P. (Biodiversity Data Journal, 2015)
The Rio Nhamundá is a poorly-known clearwater river draining the southern Guiana Shield of Brazil. In this study we report the findings of a preliminary ichthyological survey, focusing on catfishes (Siluriformes). We identify a total of 36 species (31 genera, seven families) from the Nhamundá, including 11 species already recorded from the river. Overall, our survey results show that even rapid surveys can provide important information on Amazon fish biodiversity, suggesting potential new species, providing range extensions for nominal species, and additionally highlighting taxa in need of taxonomic revision and genetic study. As well as the traditional forms of data collected on biodiversity surveys (i.e. preserved specimen vouchers), our study also provides "new" types of data in the form of DNA barcodes and images of fishes exhibiting colouration in life, information that will be invaluable in future work addressing difficult groups. O Rio Nhamundá é um rio de água clara, pouco conhecido, que drena parte do Escudo das Guianas em território brasileiro. Nesse estudo, nós reportamos os resultados de um levantamento ictiofaunístico preliminar dessa área, tendo como foco os bagres (Siluriformes). Nós identificamos um total de 36 espécies (31 gêneros, sete famílias) provenientes de nossa coleta, e adicionamos 11 espécies já conhecidas para o rio. De maneira geral, os resultados de nossa pesquisa mostram que mesmo levantamentos rápidos podem gerar informações importantes sobre a biodiversidade de peixes amazônicos, sugerindo potenciais espécies novas, ampliando a área de distribuição de espécies, além de apontar a necessidade de revisões taxonômicas e estudos genéticos para alguns taxa. Para além das formas tradicionais de dados coletados em pesquisas de biodiversidade (i.e. espécimes preservados), nosso estudo fornece "novas" formas de dados, como DNA barcodes e imagens com o padrão de coloração dos espécimes vivos, informações essas que serão de valor inestimável para futuros estudos que abordem grupos taxonômicos difíceis. © Collins R et al.